(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
It is known that in our country, two major categories of grain products are produced in the largest quantities: flour and semolina. The next places are starch, molasses, alcohol and other products. Flour is a product produced in the process of crushing grain. If it is obtained only from the inner part of the grain - the endosperm - this type of flour is called whole meal flour when ground together with the husks and bran. Grains of wheat, rye, triticale, small amounts of oats, buckwheat, barley, corn and other crops are used for flour production.